"Where Are the Bathrooms?": Academic Library Restrooms and Student Needs. Issue 5 (4th July 2017) - Margolin, Stephanie; Poggiali, Jennifer
ABSTRACT: This article investigates bathrooms, paying specific attention to those in academic libraries. The authors describe how bathrooms have been considered in the library literature for the past century and challenges to changing the status quo. Finally, this work sets the stage for future inquiry. Research materials come from a range of sources: historical library literature, building codes, social science theory and research that address the issues around bathroom taboos, and checklists for assessing bathrooms. The authors propose librarians and library administrators reconsider all aspects of their own bathrooms: location, features, equity/inclusiveness, and maintenance in service to their patrons.